CNT-enhanced electrochemical property and sodium storage mechanism of Pb(NO3)2 as anode material for Na-ion batteries. (1st July 2015) - Lin, Xiaoting; Li, Peng; Shao, Lianyi; Zheng, Xi; Shui, Miao; Long, Nengbing; Wang, Dongjie; Shu, Jie
Graphical abstract: Highlights: Pb(NO3 )2 is reported at the first time as sodium storage material. Pb(NO3 )2 /CNT is prepared by a simple solution method. Pb(NO3 )2 /CNT shows enhanced cycling and rate capabilities. The sodiation mechanism in Pb(NO3 )2 is firstly studied by in-situ method. Abstract: By using carbon nanotube (CNT), Pb(NO3 )2 /CNT is fabricated by a solution method and investigated for the first time as probable anode materials for sodium-ion batteries. For comparison, pristine Pb(NO3 )2 and Pb(NO3 )2 /carbon black (CB) are also prepared by the same solution method. Electrochemical results show that Pb(NO3 )2 /CNT can deliver an initial charge capacity of 285.7 mA h g −1, which is much higher than the pristine Pb(NO3 )2 (203.8 mA h g −1 ) and Pb(NO3 )2 /CB (252.1 mA h g −1 ). After 50 cycles, Pb(NO3 )2 /CNT still maintains a sodium storage capacity of 112.9 mA h g −1 . Furthermore, it also shows outstanding rate property compared with other two samples. All the enhanced results can be attributed to the introduction of crosslinked CNTs in the composite, which provide good electronic conductive pathways interconnecting Pb(NO3 )2 particles and maintain the whole nano-micro structure upon repeated cycles. The reaction mechanism of Pb(NO3 )2 with Na is studied by various in-situ and ex-situ techniques. It can be found that Pb(NO3 )2 /CNT irreversibly decomposes into Pb, NaNO3, NaN3, and Na2 O, and then the resulting metal Pb will further react with Na to form Nax Pb alloys during the initial discharge process. In contrast, the charge process is mainly associated with the de-alloying reaction of Nax Pb to the formation of Pb.